SETYA NOVANTO DALAM PERSIDANGAN KASUS KTP ELEKTRONIK ANALISIS SEMIOTIKA FOTO JURNALISTIK - Munggaran, Nantia Rena Dewi (PRoListik : Jurnal Ilmu Komunikasi, 2022)
Many media reported the figure of Setya Novanto. But the media were not highlighting the achievements of the politician from the Golkar Party as chairman of MPR, his name is often associated with various legal cases. The e-KTP corruption case has frustrated his political career and had to spend 15 years in prison. Following news Novanto trial in the case of e-KTP in the media which is equipped with photographs of the trial, makes the author tick for analyzing using semiotics. The author analyzes 3 (three) photos that can represent the entire trial photos, the photos titled news “Setya Novanto Didakwa Intervensi Proyek e-KTP dan Rugikan Negara Rp 2,3 Triliun” Garry Andrew Lotulung’s work on kompas.com December 13, 2017, “Setya Novanto Terima Hakim Lanjutkan Sidang Korupsi e-KTP” Andry Novelino’s work on cnnindonesia.com, and “Setya Novanto Ditinggalkan” by Alif Ichwan, which was the headline of Kompas Daily on May 1, 2018. The author used Charles Sander Peirce’s semiotic analysis method to obtain meaning through the disclosure of signs in Setya Novanto’s photographs in the trial’s report. From the analysis it was concluded that the media recorded the figure of Setya Novanto in the trial of the e-KTP case as a figure full of lies, full of intrigues to fight the law in his own favor. But at the end of the trial the media caught the sadness and disappointment on Setya Novanto’s face. While the meaning through the expression of signs in Setya Novanto’s photographs during the trial was seen from facial expressions, body gestures, and eye gazes.